The Effectiveness of The Use of Science Quartet Learning Media in Junior High Science Learning: Efektivitas Penggunaan Media Pembelajaran Kwartet Sains Pada Pembelajaran IPA SMP - Mauliah, Sailatul; Wulandari, Ria (Universitas Muhammadiyah Sidoarjo, 2023)
This study investigates the efficacy of Science Quartet learning media in middle school science education, specifically focusing on taxonomy comprehension. The research aims to ascertain the effectiveness of this approach by analyzing teacher management, student engagement, learning outcomes, and student responses. Employing a quantitative experimental design with pretest-posttest methodology, the study collected data through observation sheets, tests, and questionnaires. Descriptive statistics and the N-Gain test were employed to analyze implementation, student activities, and cognitive learning outcomes. Results reveal a high level of implementation (2.75), excellent student engagement (81.3%), and substantial cognitive learning improvements (average N-Gain of 0.31). Notably, students responded positively (average score of 85.4) to the Science Quartet approach. This research underscores the effectiveness of Science Quartet in enhancing science education, particularly in the context of taxonomy understanding, thus providing valuable insights for science educators globally. Highlights: Innovative Approach: The study introduces the Science Quartet learning media as an innovative method to enhance middle school science education, particularly focusing on taxonomy comprehension. Positive Learning Outcomes: The research demonstrates significant cognitive learning improvements (average N-Gain of 0.31) among students who were exposed to the Science Quartet approach, highlighting its effectiveness in promoting better understanding and retention of scientific concepts. Global Implications: The findings provide valuable insights for science educators worldwide, emphasizing the potential of the Science Quartet approach to engage students, improve learning outcomes, and create a positive learning environment in science classrooms. Keywords: Science Quartet, Middle School Science Learning, Taxonomy Education, Effectiveness, Student Engagement